Solving Lotka-Volterra prey-predator model using implicit multistep method of order four - Marhisham, Haizad Hakimi; Syahirbanun Isa, (Enhanced Knowledge in Sciences and Technology, 2023)
This paper study the applicability, and the efficiency of the implicit multistep method of order four, resulting in the system of first order nonlinear ordinary differential equations (ODEs). A system of first order nonlinear ODEs have been considered with initial conditions which are Lotka-Volterra prey-predator model. The model has been solved by implicit multistep method of order four using different step size, h with the help of MATLAB. The absolute error analyzed are also carried out explicitly in the framework. The numerical results of the model have been calculated and compared with Runge-Kutta method of order four and MATLAB ODE solver (ode45). Moreover, for the Lotka-Volterra prey-predator model, a comparison of the computation is compared and is worked out to illustrate the general advantage of proposed method.